The Effect Of Self-Efficacy, Organizational Culture, Work Ethic And Job Satisfaction On The Teacher’s Performance Of Public Madrasah Aliyah In North Sumatra, Indonesia - Muksin Batubara; Zainuddin; Yasaratado Wau; Nasrun (International Journal of Science, Technology & Management, 2021)
The purpose of this study was to determine and study the teacher performance model of Madrasah Aliyah Negeri (MAN) which was built based on the associative causal relationship between exogenous variables and endogenous variables: (1) the effect of self-efficacy on teacher work ethics, (2) the influence of organizational culture on work ethics. , (3) the influence of self-efficacy on job satisfaction, (4) the influence of organizational culture on job satisfaction, (5) the effect of self-efficacy on teacher performance, (6) the influence of organizational culture on performance, (7) the effect of work ethic on performance, and (8) the effect of job satisfaction on teacher performance. The methods used to achieve the objectives of this study are survey, sampling and quantitative methods. The population of this research is MAN teachers in North Sumatra Province, amounting to 1177 teachers (sampling frame) and involving 298 respondents (proportional random sampling). This research is also classified as an explanatory study which explains that to determine the magnitude of the influence of a variable with other variables, both direct and indirect effects can be used path analysis. The results of this study are (1) self-efficacy has a positive direct effect on work ethic, (2) organizational culture has a positive direct effect on work ethic, (3) self-efficacy has a positive direct effect on job satisfaction, (4) organizational culture has a positive direct effect on satisfaction. work, (5) self-efficacy has a positive direct effect on teacher performance, (6) organizational culture has a positive direct effect on performance, (7) work ethic has a positive direct effect on performance, and (8) job satisfaction has a positive direct effect on the performance of MAN teachers in North Sumatra. Overall, the perfect fit model has been tested, a model of MAN teacher performance improvement which is proportionally influenced directly and indirectly by job satisfaction, work ethic, self-efficacy, and MAN organizational culture.